Cardiorespiratory fitness and risk of all-cause, cardiovascular disease, and cancer mortality in men with musculoskeletal conditions - Lemes, Ítalo Ribeiro [UNESP]; Sui, Xuemei; Fritz, Stacy L.; Beattie, Paul F.; Lavie, Carl J.; Turi-Lynch, Bruna Camilo [UNESP]; Blair, Steven N. (Human Kinetics, 2019)
Background: To investigate the association between cardiorespiratory fitness and risk of cardiovascular disease, cancer, and all-cause mortality in men with musculoskeletal conditions. Methods: Participants were 12,728 men (mean age 47.0 [9.3] y) with a history of musculoskeletal conditions (including joint pain, low back pain, stiff joints, arthritis, osteoporosis, or gout) and were followed for all-cause mortality to December 31, 2003. Fitness was quantified by maximal treadmill exercise test and was categorized for analysis as low, moderate, and high performance. Cox proportional hazards regression was used to calculate hazard ratios and 95% confidence intervals. Results: Overall, the multivariable-adjusted hazard ratios and 95% confidence intervals for mortality across incremental fitness categories were 1.00 (reference), 0.45 (0.30–0.68) and 0.35 (0.22–0.53), linear trend P < .01 for all-cause, 0.50 (0.23–1.10) and 0.29 (0.12–0.71), linear trend P = .02 for cardiovascular disease, and 0.38 (0.20–0.74) and 0.40 (0.20–0.80), linear trend P = .01 for cancer mortality. Conclusion: Among men with musculoskeletal conditions, higher fitness is associated with lower risk of death by cardiovascular disease, cancer, or any cause, independent of other risk factors.
Keywords: Bone and joint condition; Cohort study; Death; Exercise capacity